2015
DOI: 10.1111/jpn.12334
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation of rutin on lactation performance, ruminal fermentation and metabolism in dairy cows

Abstract: The effect of long-term dietary supplementation with rutin on the lactation performance, ruminal fermentation and metabolism of dairy cows were investigated in this study. Twenty multiparous Chinese Holstein cows were randomly divided into four groups, and each was offered a basal diet supplemented with 0, 1.5, 3.0 or 4.5 mg rutin/kg of diet. The milk yield of the cows receiving 3.0 and 4.5 mg rutin/kg was higher than that of the control group, and the milk yield was increased by 10.06% and 3.37% (p < 0.05). O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Stoldt et al (47) found that rutin (glucrohamnoside of quercetin) had no effect on methane production or energy metabolism of Holstein cows housed in respiration chambers. Cui et al (113) reported that the addition of 3.0 mg rutin/kg to diets on multiparous Chinese Holstein cows increased milk yield (10.06 %) in the long term and improved metabolism and digestibility of dairy cows. Other experiments using Holstein cows and supplementation of 60 mg/kg body weight of alfalfa flavonoid extract increased the valeric acid:total volatile fatty acid ratio, the composition of milk, nutrient digestion, and had a tendency to increase the population of Butyrivibrio fibrisolvens (114).…”
Section: Flavonoidsmentioning
confidence: 99%
“…Stoldt et al (47) found that rutin (glucrohamnoside of quercetin) had no effect on methane production or energy metabolism of Holstein cows housed in respiration chambers. Cui et al (113) reported that the addition of 3.0 mg rutin/kg to diets on multiparous Chinese Holstein cows increased milk yield (10.06 %) in the long term and improved metabolism and digestibility of dairy cows. Other experiments using Holstein cows and supplementation of 60 mg/kg body weight of alfalfa flavonoid extract increased the valeric acid:total volatile fatty acid ratio, the composition of milk, nutrient digestion, and had a tendency to increase the population of Butyrivibrio fibrisolvens (114).…”
Section: Flavonoidsmentioning
confidence: 99%
“…Polyphenolic compounds, including flavonoids, occur in almost all plants and represent one of the most prevalent classes of PSM ingested by ruminants. Flavonoids are known to modulate several parameters of rumen fermentation, especially to increase the number and diversity of rumen microbiota (Balcells et al., ; Cui et al., ). Similarly, saponins comprise a vast group of low molecular weight secondary plant constituents which occur in plants used for cattle feeding, predominantly alfalfa and clovers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the direct effect on ruminal processes, both flavonoids and saponins have been described as health‐promoting, disease‐preventing feed additives. Flavonoids used as feed supplements in the long term tended to increase the milk yield, improve the metabolism and digestibility of the dairy cows (Cui et al., ), affect the humoral immune response, and enhance growth in young calves (Yaghoubi, Ghorbani, Rahmani, & Nikkhah, ). Eventually, the antioxidant and anti‐inflammatory properties of flavonoids as well as their ability to moderate the activity of several metabolic enzymes make those phytocompounds very favorable in dairy cows since they can experience oxidative stress during the peripartum period (Kobayashi, Miyazawa, Kamei, Abe, & Kojima, ), whereas saponins’ usage as phytogenic feed additives results from their numerous biological activities, including immunostimulatory, anti‐inflammatory, hepatoprotective, antibacterial, antiviral, antifungal, and antiparasitic properties (Francis, Kerem, Makkar, & Becker, ; Sprag, Light, & van Staden, ).…”
Section: Introductionmentioning
confidence: 99%
“…In livestock, rutin and quercetin can have positive effects, although a little different: the addition of rutin to diets of dairy cows tends to increase the milk yield and improve the digestibility of feed (Cui et al . ), while quercetin inhibits the growth of parasites and bacteria (Vijaya and Ananthan ; Dupuy et al . ).…”
Section: Introductionmentioning
confidence: 99%